Risk factors for dengue with warning signs, in the emergency department of a Public Hospital. A case- control study - García-Vilca, Lesly (2024)
Objective: To evaluate the risk factors for dengue with warning signs in patients seen in the emergency department of a Public Hospital located in Trujillo, Perú, during the period from January to October 2023. Materials and methods: A case- control study was conducted at the emergency department of the Hospital Distrital Jerusalén in Trujillo, Perú, between January and October 2023. In the data analysis, chi-square and Fisher tests were used to identify variables associated with warning signs of dengue (p<0.05); subsequently, multivariate logistic regression was performed to calculate the adjusted Odds ratio (ORa) with its respective 95% confidence intervals. Results: We included 92 cases of dengue with warning signs and 184 controls without warning signs. Age, education level, arterial hypertension, obesity and previous infection were significantly associated (p<0.05) to dengue with alarm signs. Logistic regression identified the following as risk factors for dengue with warning signs: arterial hypertension with an ORa of 8.27 (CI 95% 1.20-56.6), obesity with an ORa of 24.4 (CI 95% 7.58-78.9), previous infection with an ORa of 4.99 (CI 95% 1.75-14.2), age ≤ 14 years with an ORa of 5.88 (95% CI 2.08-19.61) and age ≥ 60 years with an ORa of 1.76 (95% CI 1.61-3.00). Conclusion: Arterial hypertension, obesity, previous dengue infection, age ≤ 14 years, and ≥ 60 years are risk factors for dengue with alarm signs.